Evaluation of Hand-Scaling Skills of Dental Hygienist Students: Identification of Contact Between Hand-Scaler Blade Tip and Tooth Surface - Tomoko Yui; Sung-Gwi Cho; Yuki Sato; Yasuaki Orita; Ming Ding; Jun Takamatsu; Takahiro Wada; Tsukasa Ogasawara (IEEE Access)
Dental hygienist students require a self-learning simulator to learn the correctness of hand-scaling techniques. An essential technique in hand scaling is the maintenance of contact between the tip of the hand-scaler blade and the tooth. However, imaging-based methods cannot effectively reveal this contact because the gingiva and buccal mucosa conceal the blade. Therefore, this study aimed to propose a method to identify the appropriate contact state of the blade with the tooth by using an inertial measurement unit (IMU) attached to the hand scaler and a force sensor attached to the target tooth. The hand-scaling motion was measured in an experiment in which participants were instructed to use the tip or middle of the blade to contact the tooth. The contact state of the blade, whether it was the tip or the middle, was identified using 18 features, including the average and standard deviation of nine dimensions of force, acceleration, and angular velocity with a support vector machine (SVM). The results showed that the model using all 18 features could classify the contact state with an accuracy of 97.1%. Furthermore, the accuracy was 95.9% with the 12 features from IMU alone, which was not significantly different from the accuracy with 18 features. The accuracy was 88.8% with six features from the force sensor alone. These results indicate that the IMU alone can identify the correct contact state, highlighting the possibility of creating a realistic simulator for training dental hygienists in evaluating the blade-contact state.